A career in books : a novel about friends, money, and the occasional duck bun - Gavino, Kate (Plume, 2022)
"Shirin, Nina, and Silvia have just gotten their first jobs in publishing, at a University Press, a traditional publisher, and a trust-fund kid's "indie" publisher, respectively. And it's... great? They know they're paying their dues and the challenges they meet (Shirin's boss just assumes she knows Cantonese, Nina cannot get promoted by sheer force of will, and Silvia has to deal with daily microaggressions) are just part of "a career in books." When they meet their elderly neighbor, Veronica Vo, and discover she's a Booker Prize winner dubbed the "Tampax Tolstoy" by the press, each woman finds a thread of inspiration from Veronica's life to carry on her own path. And the result is full of twists and revelations that surprise not only the reader but the women themselves"--